Guardian willingness to vaccinate adolescent daughters against human papillomavirus for cervical cancer prevention in hard-to-reach communities in Mandera County, Kenya - Mohamed, Ifrah S.; Muchiri, Joseph M.; Makokha, Francis W. (International Journal Of Community Medicine And Public Health, 2023)
Background: Cervical cancer is the fourth most frequent disease in women, and in 2020, there was an estimated 604,127 new cases and 342,831 fatalities worldwide. Despite the fact that cervical cancer can be easily treated if detected early, Sub-Saharan Africa suffers the greatest incidence of cervical cancer morbidity and mortality. The purpose of this study was to ascertain parents’ readiness to protect teenage girls from Human Papillomavirus. Methods: The study used a cross-sectional descriptive strategy conducted among guardians of adolescent girls in rural area in Mandera. A simple random sampling technique was adopted and data was collected through key informant interviews, focus group discussions, and pretested interviewer-administered questionnaires. Results: The study’s findings demonstrated that while parental understanding of the HPV vaccine was low in our study area, parental awareness was high. This resulted in low parental acceptance of the HPV vaccine, which in turn resulted in low uptake. The study participants’ degree of vaccination acceptance was low (30%), with the majority showing hesitation (54%). Socio-cultural factors and religion were identified as the main barriers to HPV vaccine acceptance among the participants. Conclusions: The findings of our study demonstrate that although guardians in the research area had a high level of awareness of the HPV vaccine, there was poor uptake of the vaccine due to low knowledge and sociocultural reasons. Despite the fact that these services were both ample and accessible.